Reductive responsive micelle overcoming multidrug resistance of breast cancer by co-delivery of DOX and specific antibiotic. Issue 40 (7th August 2019) - Cui, Yani; Yang, Yuedi; Ma, Mengcheng; Xu, Yang; Sui, Junhui; Li, Huifang; Liang, Jie; Sun, Yong; Fan, Yujiang; Zhang, Xingdong
Abstract : The redox-degradable nano-micelle-reversed drug resistance by combination chemotherapy strategy of salinomycin (SL) that could specifically inhibit A/MCF-7 cells and a traditional broad-spectrum antitumor drug, doxorubicin (DOX). Abstract : The residual tumor cells after chemotherapy, even in very small numbers, are generally drug-resistant and invasive, which might result in the progress of tumor metastasis and recurrence. In this research, a new combination chemotherapy strategy of salinomycin (SL) that could selectively inhibit multidrug-resistant tumor cells and a traditional broad-spectrum antitumor drug, doxorubicin (DOX), based on redox-degradable nano-micelles was developed to overcome drug resistance in vitro . The results in vitro indicated that DOX + SL co-loaded nano-micelles could not only escape from the drug efflux of adriamycin-resistant MCF-7 cells (A/MCF-7) but also penetrated and infiltrated into 3D-cultured MCF-7 and 4T1 tumor spheres in vitro more effectively, resulting in a strong antiproliferative effect. In the allogeneic metastatic 4T1 tumor model, the combination chemotherapy of DOX + SL encapsulated in nano-micelles effectively suppressed tumor growth with no splenomegaly and no other major tissue damage, and reversed the EMT progress, and inhibited tumor recurrence and metastasis more effectively after drug withdrawal.